DYNAMIC PATH OF WORKING STATUS CATEGORY IN INDONESIA : A TAWHID STRING RELATION (TSR) PERSPECTIVE - Muhammad Zilal Hamzah; Jadi Suriadi (Universitas Trisakti, 2012)
The core objective of this paper is to show and evaluate evidence of working status of people under labor forced in Indonesia within one and half decade recently. As well understood that labor forced had been classified under working status category namely self employment, micro-entrepreneurs, medium and large entrepreneurs formal employed, informal employed and unemployment. Methodology of tawhid string relation (TSR) called to elaborate, identify and evaluate the cased in holistic manner under light of Oneness of God.Design/Methodology/approach-This paper presents the data of Indonesian semi annual labor forced survey from National Statistic Bureau (BPS) within 1994 to 2011. The collected data, quantitatively is presented into working status category. It will be evaluated by TSR method.